2022
DOI: 10.3389/fphys.2022.867444
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Nucleocapsid Protein is Associated With Lower Testosterone Levels: An Experimental Study

Abstract: The ongoing COVID-19 pandemic represents an extra burden in the majority of public and private health systems worldwide beyond the most pessimistic expectations, driving an urgent rush to develop effective vaccines and effective medical treatments against the SARS-CoV-2 pandemic. The Nucleocapsid structural viral protein is remarkably immunogenic and hugely expressed during infection. High IgG antibodies against Nucleocapsid protein (N protein) levels were detected in the serum of COVID-19 patients, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This highlights the complexity of male hormone level regulation. Interestingly, in another study by Jorge Hallak 50 and colleagues, inoculation of the SARS-CoV-2 nucleocapsid protein into the testes, epididymis, prostate, and seminal vesicles of rats did not show significant histological changes. However, the treated group exhibited higher sperm counts and lower testosterone levels, while LH levels did not change significantly.…”
Section: Discussionmentioning
confidence: 94%
“…This highlights the complexity of male hormone level regulation. Interestingly, in another study by Jorge Hallak 50 and colleagues, inoculation of the SARS-CoV-2 nucleocapsid protein into the testes, epididymis, prostate, and seminal vesicles of rats did not show significant histological changes. However, the treated group exhibited higher sperm counts and lower testosterone levels, while LH levels did not change significantly.…”
Section: Discussionmentioning
confidence: 94%
“…In an experimental study, Carrasco et al. found that the serum T levels in rats inoculated with the isolated N protein were significantly lower than those in the control group ( 44 ). Compared to healthy men, COVID-19 patients were accompanied by elevated serum LH levels and reduced T/LH ratios, suggesting possible subclinical impairment of male gonadal function ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira et al ( 74 ) suggest that a decreased testosterone/luteinizing hormone ratio correlated with high levels of C-reactive protein and white blood cell count, reported by some authors, can mean a transient stage of hypogonadism. In an experimental study, Carrasco et al ( 75 ) inoculated in rats nucleocapsid protein, that have high IgG antibodies against it in COVID-19 patients and found low serum levels of testosterone and free testosterone in these rats compared with a control group. They suggest that this hormone imbalance can be linked with a post-COVID-19 syndrome hypogonadism.…”
Section: Discussionmentioning
confidence: 99%